Clinical Applications of Botulinum Toxin in Oral and Maxillofacial Surgery: Clinical Applications of Botulinum Toxin in Oral and Maxillofacial Surgery - AlAhmary, Ahmed Wallan; Alqhtani, Sabrin Moshabab; Alshahrani, Bshayer Abdullah; Alkaram , Wadiah Abdullah; Alhadad, Bayan Saeed; Elmarakby, Ahmed M. (Open Access Macedonian Journal of Medical Sciences, 2020)
Botulinum toxin is a toxin produced by Clostridium botulinum bacteria. This toxin has eight known serotypes, among which both A and B are currently used in medicine. Its mechanism of action acts on inhibiting acetylcholine release at neuromuscular junctions following its local injection. This toxin has wide applications in dentistry in general and in oral and maxillofacial (OMF) surgery in particular. It can be applied in the management of temporomandibular joint disorders, neuropathic facial pain, facial nerve palsy, hypertrophy, and hyperactivity of masticatory muscles as examples. At present, it can be used in cosmetic treatment in the facial region to control wrinkles and asymmetry. The therapeutic effects of these toxins are temporary and relatively safe if used in an appropriate manner. This review was aimed to identify the uses of botulinum toxin in surgical and non-surgical treatment of OMF problems, the types of treatment available, and benefits of those treatments.